The Revolting Body of Poetry. - Shinabargar, Scott (Chiasma Ser., 2016)
If the transgressions of modern French poetry have been amply noted at thematic and formal levels, they remain largely unremarked at the most visceral level of reading. Indebted to, while problematizing the Kristevan concept of sémiotique , Scott Shinabargar's The Revolting Body of Poetry reveals how the very "matter" of key works forces us to enact these transgressions, when articulating textures of offensive lexica and imagery. While certain phonemes provide access to previously untapped forces, first apparent in Baudelaire and Lautréamont, compulsive repetitions produce expressive inflation, diffusing any initial impact. Césaire and Char, however, demonstrate an acquired control of these forces, intensity contained. Shinabargar concludes with a survey of contemporary poets, inviting readers to consider the legacy of revolting poetics.